Assessing the Effects of Organizational Justice on Organizational Commitment in Malaysia’s SME Sector - Manshor, R.; Muda, M. S.; Salleh, A. M. M.; Razak, F. Z. A.; Kamaazura, A.B. (Journal of Advanced Research in Business and Management Studies, 2020)
The current study is aimed to explore factors influencing organizational commitment among Malaysian SME employees. A total of 384 employees from Malaysian SME companies had completed both the self-reported organizational commitment scale and organizational justice scale. The results revealed that procedural justice, distributive justice and informational justice are significantly and positively related to organizational commitment. Structural equation modeling indicated that the proposed theoretical model has a good level of fit.